Science fiction and medicine: devising a framework to support the development medical artifacts - Costa, Maria Alexandra Cardoso (2021)
With technological advances, the human being becomes more and more reliant on technology. We use technology to work, to improve our social experiences, to learn, among many other activities. Medicine is no exception to this. It is common to hear about concepts originated on Science Fiction coming to life in areas such as spatial exploration or even communication. It is important to realise how Science Fiction helps teams working in those domains, as well as understand what consumers expect for the future. However, we rarely hear about Science Fiction directly influencing Medicine. Has this field also benefited from Science Fiction to create new or enhanced existing artifacts? This literary and cinematic genre pushes the boundaries of what is thought "possible" by idealizing artifacts that go beyond what is conceivable in their time. It is an outlet for those who want to imagine what the future might hold, without forgetting to distinguish the possible or plausible from the fantastical. In this dissertation, we go through how Science Fiction can be used as a guide to developing Medical Artifacts, as well as devise a framework that has the potential to help their developers make more informed decisions about the characteristics of those artifacts. MADIS - Medical Artifact Design Inspired by Science Fiction - is a framework that incorporates the knowledge acquired during the research and interviews with medical professionals to create a tool which supports the development of Medical Artifacts through the lens of Science Fiction.